Age-specific Parkinson disease risk in GBA mutation carriers: information for genetic counseling - Rana, Huma Q. (2012)
PURPOSE: We sought to estimate age-specific risk of Parkinson disease in relatives of patients with Gaucher disease, who are obligate carriers of GBA mutations and who were not ascertained by family history of Parkinson disease. METHODS: A validated family history of Parkinson disease questionnaire was administered to 119 patients with Gaucher disease who were evaluated at the Mount Sinai School of Medicine from 2009 to 2012; the ages of their parents, siblings, and children, history of Parkinson disease, age at onset of Parkinson disease, and ethnic background were obtained. Kaplan–Meier survival curves were used to estimate age-specific Parkinson disease penetrance among parents of patients with Gaucher disease, who are obligatory GBA mutation carriers. RESULTS: Two participants with Gaucher disease were affected by Parkinson disease (5.4% of those who were 60 years or older). Of the 224 informative parents of patients with Gaucher disease, 11 had Parkinson disease (4.9%). Among the parents (obligatory carriers), cumulative risk of Parkinson disease by ages 65 and 85 was estimated to be 2.2% ±2.1% and 10.9% ±7.2%, respectively. CONCLUSION: We provide useful age-specific estimates of Parkinson disease penetrance in patients with Gaucher disease and GBA heterozygous carriers for genetic counseling. Although GBA mutations may increase the risk for PD, the vast majority of patients with Gaucher disease and heterozygotes may not develop the disease. Further studies are needed to identify what modifies the risk of Parkinson disease in GBA mutation carriers.